Nanotechnologies for the Life Sciences 2003
DOI: 10.1002/9783527610419.ntls0054
|View full text |Cite
|
Sign up to set email alerts
|

Toxicity of Nanomaterials – New Carbon Conformations and Metal Oxides

Abstract: The sections in this article are Introduction Nanoscale Materials and Adverse Health Effects: Precautionary Measures Hazard Identification and Exposure Estimation Production and Use of “New Carbon Modifications” and Metal Oxides Health Aspects Uptake and Possible Transport, Depots, and Accumulation in Living O… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2006
2006
2008
2008

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 94 publications
0
5
0
Order By: Relevance
“…They are also produced for food and cosmetic chemistry and many other technical applications. 8 The increasing production, particularly of single-walled carbon nanotubes, will enhance the possible exposure at workplaces, packing stations, and during application of these products. 9 In addition, waste treatment and containment at the end of a product's life cycle must be considered.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…They are also produced for food and cosmetic chemistry and many other technical applications. 8 The increasing production, particularly of single-walled carbon nanotubes, will enhance the possible exposure at workplaces, packing stations, and during application of these products. 9 In addition, waste treatment and containment at the end of a product's life cycle must be considered.…”
Section: Introductionmentioning
confidence: 99%
“…Nanostructured materials come into contact with biological systems through their use in drug delivery systems or for gene transfer. They are also produced for food and cosmetic chemistry and many other technical applications .…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In connection to nanoparticles it must be asked how man-made nanostructures can possibly interact or influence biological systems? On the one hand, nanosystems are specifically engineered to interact with biological systems for particular medical or biological ap plications ( ). On the other hand, the large scale production of nanoparticles for either non-medical applications or as side products of combustion processes may have an effect on organisms in all parts of our environment.…”
Section: Introductionmentioning
confidence: 99%
“…It must be underlined that ROS is used as a biomarker for oxidative cell stress. It has been shown that lung cells respond to oxidative stress significantly (Krug et al 2006;Nel et al 2006).…”
Section: The Relationship Of Pges To Human Healthmentioning
confidence: 99%